Učinki uporabe plavalnih očal in dihalke pri plavalnih začetnikih z izrazitim strahom pred vodo - Misimi, Fatmir (Šport (Ljubljana), 2023)
The aim of the study was to investigate the effect of the usage of goggles and snorkels during the learn-to-swim program on the aquatic skills of young non-swimmers without fear of water. We randomly divided forty children with a fear of water (aged 10-11 years) into a group that used goggles and snorkels and a group that did not use these aids during the learn-to-swim program. The majority of participants improved their aquatic skills as a result of the learn-to-swim intervention. The comparisons of the in- tervention effects between the groups showed that the learning improvement in water entry, back gliding, and prone swimming scores were bigger in OD group than in ne-OD group. At the contrary, the intervention effect was lower in the blowing bubbles scores in OD group than in ne-OD group. The results of present study highlight the positive and negative effects of the usage of goggles and snorkels in learn-to-swim programs.
Keywords: dihalke; neplavalci; plavalna očala; plavanje; pripomočki; strah; šport; učenje